Missouri guide for pavement rehabilitation - Missouri. (Missouri Dept. of Transportation, Research, Development and Technology Division, 2002)
Different rehabilitation treatments were evaluated for effectiveness on Missouri State roads. Existing Missouri performance data for predominant treatments was analyzed. Performance information for treatments seldom used in Missouri was gathered from other states.
"November, 2002" -- cover.
Cover title.
Different rehabilitation treatments were evaluated for effectiveness on Missouri State roads. Existing Missouri performance data for predominant treatments was analyzed. Performance information for treatments seldom used in Missouri was gathered from other states.
Keywords: Pavements / Maintenance / Missouri. / tlsh; Road materials / Research / Missouri.; Transportation / Research / Missouri.